New species of Australopericoma Vaillant (Diptera: Psychodidae) from the Brazilian semiarid region and key to males of the genus. Issue 11 (26th March 2016) - Cordeiro, Danilo Pacheco; Bravo, Freddy; Araújo, Maíra Xavier
ABSTRACT: A new species of moth fly, Australopericoma paraibana sp. n., is described from areas of the Brazilian semiarid region, in the states of Paraíba and Bahia, north-eastern Brazil. A key to males of Australopericoma and morphological remarks on Australopericoma caudata (Satchell) are also provided.